The Effect of Net Profit Margin (NPM) and Debt to Equity Ratio (DER) on Dividend Policy Dividend Policy Listed on the IDX30 Index for the period 2019-2023 - Refaldi, Alan; Kardinal, Kardinal (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the effect of Net Profit Margin (NPM), and Debt to Equity Ratio (DER), on Dividend Policy both partially and simultaneously. The research adopts a quantitative approach with a causal research design. The data used is secondary data derived from the annual financial statements of companies listed on the IDX30. The sampling technique employed is purposive sampling, resulting in 15 companies selected as the research sample. Data analysis techniques include classical assumption tests and multiple linear regression to examine the effect of each independent variable on the dependent variable, both partially and simultaneously. The partial test results indicate that NPM has a positive and significant effect on the Dividend Payout Ratio (DPR), and DER has a negative and significant effect on DPR. Based on the simultaneous test results, it is shown that NPM and DER collectively influence dividend policy.